Against growing synonymy: Identification pitfalls of Hepatozoon and Schellackia demonstrated on North Iranian reptiles - Zechmeisterová, Kristína; Javanbakht, Hossein; Kvičerová, Jana; Široký, Pavel (European journal of protistology, 2021)
The analyses of molecular data represent an effective tool for increasing the credibility of taxonomy and facilitate the description of species. Nevertheless, in haemoprotozoa, the growing amount of available sequential data is not matched by the still limited number of well-defined species. We identified four protistan haemoparasites in North Iranian reptiles: two Hepatozoon and two Schellackia species. Hepatozoon colubri and Hepatozoon ophisauri were morphologically identified in their type hosts, their partial 18S rDNA was analyzed, and thorough literature data were included in their redescription. The scarce data on the detected Schellackia spp. did not allow for their formal species description. Using an integrative approach, including morphological and geographical features, host specificity, molecular data, and the data published thus far, we face the following main difficulties hindering reliable diagnosis. (1) The lack of molecular data on well-described and named species. (2) The insufficiency of using only morphological and biological features, or only sequential data without morphology, to perform an absolutely reliable species diagnosis. (3) Typical morphological features are more substantial than metric means. (4) High risk of synonymy is present in taxonomy of blood Protista. (5) Artefacts caused by blood smear processing further complicate the correct morphological determination.
Keywords: Animals; Artefacts; Eucoccidiida; RNA, Ribosomal, 18S; Írán; plazi; Hepatozoon ophisauri; druhová specificita; Schellackia; Species Specificity; kokcidióza; Coccidiosis; DNA, Protozoan; Iran; Haemoparasites; protozoální DNA; Hepatozoon colubri; RNA ribozomální 18S; zvířata; Reptiles